Infectious sources of Histoplasmosis and molecular techniques for its identification - Bhandari, Sudip; Rayamajhee, Binod; Dhungel, Laxmi; Poudel, Sami; Gaire, Bhagwati; Shrestha, Sunil; Parajuli, Niranjan (Nepal Journal of Biotechnology, 2019)
Histoplasmosis, a fungal infection caused by Histoplasma capsulatum (H. capsulatum), acquired from contaminated soil with droppings of chicken or birds and found to be distributed in many parts of the world. The prevalence of histoplasmosis has not well studied in Nepal. The common symptoms of acute and epidemic histoplasmosis include high fever, cough, and asthenia and weight loss. Most of the infections associated with histoplasmosis are asymptomatic. People with compromised immune systems such as HIV/AIDS (PLWHA), cancer, and organ transplant recipients are at risk of developing this disease. In this review, we have summarised the current status of histoplasmosis in Nepal and molecular techniques available for its identification. To date, the significant outbreak is not reported in Nepal, but the risk of infection for the vulnerable population cannot be undermined. Appropriate preventive measures and treatment on time can reduce the burden of this fungal disease. Further, this review is also focused on molecular identification of H. capsulatum. Hence, careful considerations by concerned stakeholders for national surveillance programs and the treatment of patients on time after proper diagnosis is highly recommended.